2008
DOI: 10.1002/biot.200800067
|View full text |Cite
|
Sign up to set email alerts
|

Time‐ and media‐dependent secondary carotenoid accumulation in Haematococcus pluvialis

Abstract: The green microalgae Haematococcus pluvialis synthesizes secondary carotenoids after exposure to environmental stress, a process that is used for the biotechnological production of astaxanthin (Ax). This study reports, for the first time, the medium-dependent changes in the carotenoid pattern throughout the cultivation process as well as the exact composition of carotenoids and their fatty acid mono-and diesters using LC-MS. Secondary carotenoid formation started immediately upon exposure to nutrient depletion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 76 publications
0
10
0
Order By: Relevance
“…Maximal degradation rate of carotenoid esters under optimal reaction conditions was 89.3% (data not shown), whereas the maximal free astaxanthin recovery achieved was 63.2%. TLC detection showed that other carotenoids had also been generated in the reaction, suggesting that other carotenoid esters in the substrates such as adonirubin esters (Grewe and Griehl 2008) might have also been hydrolyzed to the free form during the reaction. Further investigations should be made to identify these by‐products and a nitrogen‐filled obturating reactor should be used to improve the efficiency of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Maximal degradation rate of carotenoid esters under optimal reaction conditions was 89.3% (data not shown), whereas the maximal free astaxanthin recovery achieved was 63.2%. TLC detection showed that other carotenoids had also been generated in the reaction, suggesting that other carotenoid esters in the substrates such as adonirubin esters (Grewe and Griehl 2008) might have also been hydrolyzed to the free form during the reaction. Further investigations should be made to identify these by‐products and a nitrogen‐filled obturating reactor should be used to improve the efficiency of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…These high-carbon lipids have been proposed as a source of sustainable oil production and thus as a highly feasible alternative in the development of third-generation biofuels. Microalgae also produce other metabolites, such as astaxanthin, lutein, arachidonic, eicosapentaenoic, and docosahexaenoic acids, which are of high economic value, and even toxins such as yessotoxins [5,6,17,36,40]. Recent research has focused on the production and isolation of commercially interesting metabolites, including those derived from microalgae, for a broad range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…DiVerent techniques are used to modify the biochemical composition of microalgae, including altered environmental parameters, such as light, salinity, or nutrients [29,37,39], and diVerent CO 2 Xow regimes during the aeration of photobioreactors, open ponds, or raceway ponds [11]. These techniques enhance the productivity of speciWc microalgal strains and have been successfully applied to obtain new sources of natural products, e.g., labeled lipids ( 13 C) [1], toxins [14], secondary metabolites (antioxidants, e.g., lutein), pigments (astaxanthin), or PUFAs such as arachidonic acid, eicosapentanoic acid, and docosahexanoic acid [5,6,17].…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient limitation such as nitrogen, phosphorus or sulfur are widely used strategies for inducing astaxanthin accumulation in Haematococcus pluvialis [57,58]. However, nutrient limitation reduces the maximum amount of biomass one can achieve, thereby reducing the total amount of astaxanthin that can be produced.…”
Section: High Valued Productsmentioning
confidence: 99%